Key cellulase components synergizing with lactic acid bacteria to degrade alfalfa lignocellulose to improve lactic acid fermentation - Ma, Linxiong; Li, Junfeng; Zhao, Wanyu; Wang, Jingyu; Li, Yanwen; Xiong, Yueying; He, Yongchao; Chu, Xiaohui; Liu, Qinhua (Frontiers in Microbiology, 2025)
Using cellulase to convert alfalfa lignocellulose into lactic acid (LA) is useful in low-temperature seasons to improve fermentation quality, but it is still unknown which specific cellulase component synergizes with lactic acid bacteria (LAB) to promote LA fermentation. This study aimed to clarify the key cellulase components that synergized with LAB when converting alfalfa lignocellulose into LA during ensiling from late fall to winter (3–20°C) over 140 days. Seven combinations of cellulase component gene-engineered Lactococcus lactis (MG1363), cellulase (EN), and a combination of Lactobacillus plantarum and cellulase (LPEN) were used as parallel treatments, with a control (CON) without treatment also used. EN degraded lignocellulose best. The pH value in the channel of converting sugars into LA was the key limiting factor for lignocellulose saccharification in LPEN. The optimal combination resulted in the fewest disaccharides (1.02 g/kg DM) and the highest conversion of water-soluble carbohydrates (WSC) to LA, up to 170%. It increased LA content to 80.0 g/kg DM maximally, since cellobiohydrolase better cooperated with MG1363 to ferment lignocellulose into LA than endoglucanase and β-glucosidase. Strong LA production was achieved by clarifying key cellulase components with cellulase component gene-engineered LAB.